A short note on the F.A.O. statistics for the porbeagle shark (Lamna nasus) in the Atlantic and its relation to other Lamnid - Fernández-Costa, José; Mejuto-García, Jaime (2010)
This document presents an overview of the recent FAO statistics on the porbeagle shark (Lamna nasus) and examines its relationship to the reported catch of one of the other important species belonging to the family Lamnidae (Isurus oxyrinchus), establishing a ratio between the two. The data suggest that there may be some inconsistencies between the statistics reported for the two species over the time series, emphasizing the need to maintain smooth coordination between the RFOs and the FAO and to set up programs aimed at the dissemination of specific information directed at the different countries, to improve the statistics of these species. It seems highly advisable to implement programs to provide information and training to fishers as well as to those involved in the processes of gathering and communicating data related to the statistics of these species at other levels.